A genome-wide association study of acenocoumarol maintenance dosage - Teichert, Martina; Eijgelsheim, Mark; Rivadeneira, Fernando; Uitterlinden, Andrė G.; van Schaik, Ron H.N.; Hofman, Albert; De Smet, Peter A.G.M.; van Gelder, Teun; Visser, Loes E.; Stricker, Bruno H.Ch (Human molecular genetics, 2009)
Several genome-wide association studies have been performed on warfarin. For acencoumarol, the most frequently used coumarin in many countries worldwide, pharmcodynamic influences are expected to be comparable. Pharmacokinetics however might differ. We aimed to confirm known or identify new genetic variants contributing to interindividual variation on stabilized acenocoumarol dosage by a GWAS. The index population consisted of 1451 Caucasian subjects from the Rotterdam study and results were replicated in 287 subjects from the Rotterdam study extended cohort. Both cohorts were genotyped on the Illumina 550K Human Map SNP array. From polymorphisms tested for association with acenocoumarol dosage, 35 single nucleotide polymorphisms (SNPs) on chromosome 16 and 18 SNPs on chromosome 10 reached genome-wide significance. The SNP with the lowest P-value was rs10871454 on chromosome 16 linked to SNPs within the vitamin K epoxide reductase complex subunit 1 (VKORC1) (P = 2.0 × 10−123). The lowest P-value on chromosome 10 was obtained by rs4086116 within cytochrome P450 2C9 (CYP2C9) (P = 3.3 × 10−24). After adjustment for these SNPs, the rs2108622 polymorphism within cytochrome P450 4F2 (CYP4F2) gene on chromosome 19 reached genome-wide significance (P = 2.0 × 10−8). On chromosome 10, we further identified genetic variation in the cytochrome P450 2C18 (CYP2C18) gene contributing to variance of acenocoumarol dosage. Thus we confirmed earlier findings that acenocoumarol dosage mainly depends on polymorphisms in the VKORC1 and CYP2C9 genes. Besides age, gender, body mass index and target INR, one polymorphism within each of the VKORC1, CYP2C9, CYP4F2 and CYP2C18 genes could explain 48.8% of acencoumarol dosage variation.